L2 Learning During Study Abroad: The Creation of Affinity Spaces - He, Xuewei (Journal of Interdisciplinary Studies in Education, 2021)
L2 Learning During Study Abroad: The Creation of Affinity Spaces is a dissertation-turned-book by Yoshifumi Fukada that explores how international students construct TL-mediated socialization through creating affinity spaces. Based on the experiences he and other international students had, Fukada utilized autobiography, autoethnography, and qualitative case studies to provide an in-depth understanding of the matter.